ANALISIS STRUKTUR MODAL DAN PROFITABILITAS USAHA MIKRO, KECIL, DAN MENENGAH PADA ERA PANDEMI COVID-19 - YOHANA TAMARA; HERU AGUSTANTO; BAMBANG HADINUGROHO (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2019)
Small and Medium Enterprises (SME’s) play strategically significant role in the political and socio-economic structure of a country. The importance of SME’s roles has directed the focus of academic research on identifying factors that could determine the performance of SME’s. This study aims to examine and analyze the effect of the company's capital structure, as measured by financial leverage level on profitability, as measured by Return On Equity (ROE) of SME’s in Surakarta, which specifically belong to food and beverage business sector. The number of observations is 90, with primary data collected in Surakarta, on August 2020 period. Statistical analysis was conducted by using Ordinary Least Square (OLS) regression and robustness check.Statistical analysis results show that Leverage has a very strong negative relationship with ROE, where these results are consistent and in line with several previous studies. Nevertheless, this study faces several limitations, especially related to the low level of financial literacy of SME’s and also the unavailability of SME’s periodic financial reports. This research is expected to contribute to provide insights for the government to prioritize financial literacy enhancement program for SME’s business owners. Furthermore, future researchers is expected to expand the object of analysis, so that they could obtain wider and more extensive data. Keywords : SME’s, capital structure, leverage, profitability, Return on Equity